Hidrogenasi Simultan Pada Pirolisis Cangkang Sawit Menjadi Bio-Oil dengan Katalis ZSM-5 - Anisa Mutamima; Syaiful Bahri; Sunarno; Wan Junaidi; Fathiyah Huwaidah (Jurusan Teknik Kimia, Fakultas Teknik, UNRI, 2023)
Increasing consumption of fossil fuels and decreasing oil production in Indonesia are the current energy problems. In order to overcome the threat of an energy crisis and optimize the potential of energy resources in Indonesia, research on renewable alternative energy is needed. One of the renewable energy sources is bio-oil. Bio-oil can be produced through the pyrolysis process of palm shell biomass using a ZSM-5 catalyst. In this study, the pyrolysis process was modified by adding hydrogen (hydrogenation pyrolysis), to produce bio-oil which has a higher calorific value. This study aims to determine the effect of pyrolysis temperature and ZSM-5 catalyst ratio on the yield of bio-oil in pyrolysis hydrogenation and to determine the physical and chemical characteristics of the resulting bio-oil. The pyrolysis hydrogenation process uses 50 grams of palm shells measuring -40+60 mesh, 500 ml silinap and a stirring speed of 300 rpm. The highest yield was obtained at a pyrolysis temperature of 320 oC and 2.5% ZSM-5 catalyst with a yield of 70.21%. The results of the physical characterization of bio-oil showed a heating value of 44.00 MJ/kg, a density of 0.972 g/ml, a viscosity of 1.021 cSt, a flash point of 49 oC, a pH of 3.8 and an acidity value of 51.51 g NaOH/g bio-oil. GC-MS analysis showed that the main ingredients of bio-oil were 50.29% acetic acid, 30.39% phenol, 8.19% methyl ester and 5.25% ethanol. The bio-oil obtained can be further processed to become an alternative energy source to replace petroleum.